Migration and work in postwar Australia: mortality profile comparisons between Australian and Italian workers exposed to blue asbestos at Wittenoom. Issue 1 (29th July 2017) - Reid, Alison; Merler, Enzo; Peters, Susan; Jayasinghe, Nimashi; Bressan, Vittoria; Franklin, Peter; Brims, Fraser; de Klerk, Nicholas H; Musk, Arthur W
Abstract : Objectives: Three hundred and thirty thousand Italians arrived in Australia between 1945 and 1966, many on assisted passage schemes where the worker agreed to a 2-year unskilled employment contract. Italians were the largest of 52 migrant groups employed at the Wittenoom blue asbestos mining and milling operation. We compare mortality from asbestos-related diseases among Italian and Australian workers employed at Wittenoom. Methods: A cohort of 6500 male workers was established from employment records and followed up at state and national mortality and cancer registries. SMRs were calculated to compare mortality with the Western Australian male population. Time-varying Cox proportional hazards models compared the risk of mesothelioma between Australian and Italian workers. Results: 1031 Italians and 3465 Australians worked at Wittenoom between 1943 and 1966. Duration of employment was longer for the Italian workers, although the concentration of exposure was similar. The mesothelioma mortality rate per 100 000 was higher in Italians (184, 95% CI 148 to 229) than Australians (128, 95% CI 111 to 149). The risk of mesothelioma was greater than twofold (HR 2.27, 95% CI 1.43 to 3.60) in Italians at the lowest asbestos exposure category (<10 fibre years/per mL). Conclusions: A hierarchy in migration, isolation and a shortage of workers led to Italians at Wittenoom incurring higher cumulative exposure to blue asbestos and subsequently a greater rate of malignant mesothelioma than Australian workers. Impact: Poor working conditions and disparities between native and foreign-born workers has had a detrimental and differential impact on the long-term health of the workforce.